2010
DOI: 10.1002/cyto.b.20542
|View full text |Cite
|
Sign up to set email alerts
|

Central memory CD4+ T cells dominate the normal cerebrospinal fluid

Abstract: Background: To use cerebrospinal fluid (CSF) immune phenotyping as a diagnostic and research tool, we have set out to establish reference values of white blood cell (WBC) subsets in CSF.Methods: We assessed the absolute numbers and percentages of WBC subsets by 6-color flow cytometry in paired CSF and blood samples of 84 individuals without neurological disease who underwent spinal anaesthesia for surgery. Leukocyte (i.e., lymphocytes, granulocytes, and monocytes), lymphocyte (i.e., T [CD4 1 and CD8

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
94
0
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(108 citation statements)
references
References 28 publications
7
94
0
7
Order By: Relevance
“…In contrast, the few immune cells circulating in the CSF are mostly T cells with a ratio of CD4 + T cells to CD8 + T cells of about 3.5 to 1 (summarized in [113]). The population of T cells found in the CSF of the ventricles and subarachnoid space contains mostly memory T cells that have characteristics of central memory T cells (T CM cells) and effector memory T cells (T EM cells) [33,123]. Animal models have provided additional evidence for the presence of yet another subset of memory T cells in the CNS that do not recirculate but rather persist in the CSF-drained spaces after previous infections [165].…”
Section: Neuroimmune Function Of the Choroid Plexuses In Healthmentioning
confidence: 99%
“…In contrast, the few immune cells circulating in the CSF are mostly T cells with a ratio of CD4 + T cells to CD8 + T cells of about 3.5 to 1 (summarized in [113]). The population of T cells found in the CSF of the ventricles and subarachnoid space contains mostly memory T cells that have characteristics of central memory T cells (T CM cells) and effector memory T cells (T EM cells) [33,123]. Animal models have provided additional evidence for the presence of yet another subset of memory T cells in the CNS that do not recirculate but rather persist in the CSF-drained spaces after previous infections [165].…”
Section: Neuroimmune Function Of the Choroid Plexuses In Healthmentioning
confidence: 99%
“…These APCs are present at low levels in the CSF, (116) or are situated in the meninges, choroid plexus, perivascular space, or brain parenchyma as astrocytes and microglial cells (92,160). Major pattern recognition receptors involved in initial sensing of pneumococci in the CNS are TLR2 (133,248), TLR4 (245), TLR9 (10), and Nod-like receptors (NLRs) (Fig.…”
Section: Pattern Recognition Receptorsmentioning
confidence: 99%
“…However, Svenningsson et al (38,39) did study normal CSF by assessing the percentages of lymphocyte subsets in CSF of 34 healthy individuals, after informed consent, with 2-or 3-color flow cytometry. In addition, we studied both absolute numbers and percentages of leukocyte, lymphocyte, T lymphocyte, and dendritic cell subsets by six-color flow cytometry in 84 individuals without neurological disease undergoing spinal anesthesia (Table 1; 40). The two published studies (38,39), as well as our data (40), showed that normal CSF is predominantly composed of CD4 þ T lymphocytes, mostly with a central memory phenotype, and in addition contains very low frequencies of B lymphocytes, NK cells, and NKT lymphocytes (Table 1).…”
Section: Cellular Composition Of Normal Csfmentioning
confidence: 99%